The Effects of Resistance Exercise Training on Skeletal Muscle Metabolism and Insulin Resistance Development in Female Rodents with Type 1 Diabetes - Mitchell J. Sammut; David P. McBey; Amit P. Sayal; C. W. James Melling (Journal of Diabetes Research)
The etiology of insulin resistance (IR) development in type 1 diabetes mellitus (T1DM) remains unclear; however, impaired skeletal muscle metabolism may play a role. While IR development has been established in male T1DM rodents, female rodents have yet to be examined in this context. Resistance exercise training (RT) has been shown to improve IR and is associated with a lower risk of hypoglycemia onset in T1DM compared to aerobic exercise. The purpose of this study was to investigate the effects of RT on IR development in female T1DM rodents. Forty Sprague Dawley eight-week-old female rats were divided into four groups: control sedentary (CS; n=10), control trained (CT; n=10), T1DM sedentary (DS; n=10), and T1DM trained (DT; n=10). Multiple low-dose streptozotocin injections were used to induce T1DM. Blood glucose levels were maintained in the 4-9 mmol/l range with intensive insulin therapy. CT and DT underwent weighted ladder climbing 5 days/week for six weeks. Intravenous glucose tolerance tests (IVGTT) were conducted on all animals following the six-week period. Results demonstrate that DS animals exhibited significantly increased weekly blood glucose measures compared to all groups including DT (p<0.0001), despite similar insulin dosage levels. This was concomitant with a significant increase in insulin-adjusted area under the curve following IVGTT in DS (p<0.05), indicative of a reduction in insulin sensitivity. Both DT and DS exhibited greater serum insulin concentrations compared to CT and CS (p<0.05). DS animals also exhibited significantly greater glycogen content in white gastrocnemius muscle compared to CS and DT (p<0.05), whereas DT and DS animals exhibited greater p-Akt: Akt ratio in the white vastus lateralis muscle and citrate synthase activity in the red vastus lateralis muscle compared to CS and CT (p<0.05). These results indicate that female rodents with T1DM develop poor glycemic control and IR which can be attenuated with RT, possibly related to differences in intramyocellular glycogen content.